Intonation in Spanish declaratives: differences between lab speech and spontaneous speech - Timothy L. Face (Universitat Autònoma de Barcelona, 2003)
The present study compares the intonation of Spanish declarative utterances in lab speech and spontaneous speech. Most studies of Spanish intonation have used lab speech, collected in an experimental setting and often scripted. This allows the researcher to control many factors, but the results cannot be assumed to be representative of spontaneous speech. The present study takes the most characteristic traits of the intonation of declarative sentences in Spanish lab speech and examines whether the same traits exist in spontaneous speech. It is shown that there are notable differences between the intonation of Spanish declaratives in lab speech and spontaneous speech. While some of the differences are minor, others are quite significant. Differences of one degree or another exist in the areas of the presence of F0 rises through stressed syllables, F0 peak alignment, downstepping, final lowering and deaccenting.